Kendala dan Strategi Penerapan QRIS pada UMKM Warkop Aim Tigander, Desa Kineppen - Ramanda Putri; Rizqy Aflaha Najmi Munthe; Selvi Selvi; Samiah BR Harahap; Siti Aisyah (Pusat Riset dan Inovasi Nasional, 2026)
This article examines the obstacles and strategies for implementing QRIS (Quick Response Code Indonesian Standard) in rural MSMEs, specifically Warkop AIM Tigander in Kineppen Village, Karo Regency, North Sumatra. Digital transformation has changed people's payment patterns, but QRIS adoption in rural areas still faces obstacles such as low digital literacy, cash habits, and resistance to change, not just technical issues. Through qualitative research methods including in-depth interviews and direct observation, it was found that although business owners are familiar with QRIS, its implementation is not optimal. Recommended strategies include community-based education, ongoing mentoring, and improving infrastructure and trust in the security of digital transactions. Support from the government and financial institutions is essential to accelerate the digitalization of MSMEs in rural areas, so that the economic benefits of digital payments can be felt more widely and equitably. This research suggests the need for policies that support the development of digital literacy, as well as intensive training so that MSMEs can adapt to technological changes and increase their competitiveness in an increasingly digital market.